PENGARUH DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG (Studi Pada Air Terjun Sikulikap) - Br Sitepu, Clarine Oktaryani; Harahap, Kartini; Siregar, Onan Marakali (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This study aims to evaluate the impact of digital marketing and word of mouth on the decision to visit Sikulikap Waterfall. The research method used is quantitative research with an associative approach. The population studied was Sikulikap Waterfall visitors. Sampling was done with purposive sampling technique. Data collection was done through questionnaires for primary data and literature study for secondary data. The analysis was conducted with validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing. The results of the research conducted show that the digital branding and word of mouth variables have a partial and significant effect on the decision to visit. Digital marketing and word of mouth variables also have a simultaneous and significant effect on decision making. The coefficient value also shows the relationship between digital marketing and word of mouth on visiting decisions is very strong with an R value of 0.710 or 71%. Adjusted R Square value is also known that digital marketing and word of mouth on visiting decisions is 49.4% while the remaining 50.6% is influenced by other variables not discussed in this study.